2005
DOI: 10.1027/0227-5910.26.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Change and Suicide

Abstract: This ecological study examined the association between seven socioeconomic indicators (GDP, unemployment rate, female labor force participation rate, alcohol expenditure, marriage rate, percentage of births outside of marriage, and indictable crime rate) and total, male, and female rates of suicide and suicide plus undetermined death in Ireland during the period 1968-2000. Analysis of the data expressed as absolute values showed highly significant associations between the socioeconomic indicators and the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 15 publications
(16 reference statements)
0
6
0
3
Order By: Relevance
“…While most studies have reported that higher unemployment is accompanied by an increase in suicide rates (Abe, 2004;Andres & Halicioglu, 2010;Berk et al, 2006;Blakely, Collings, & Atkinson, 2003;Chang, Sterne, Huang, Chuang, & Gunnell, 2010;Chen, Yip, Lee, Fan, & Fu, 2010;Chuang & Huang, 2007;Corcoran & Arensman, 2011;Fernquist, 2007;Kuroki, 2010;Lewis & Sloggett, 1998;Lin, 2006;Milner, McClure, et al, 2012;Preti & Miotto, 1999;Tsai & Cho, 2011;Yamasaki, Sakai, & Shirakawa, 2005;Ying & Chang, 2009), a smaller number of studies have found no or mixed evidence of this association Crawford & Prince, 1999;Lucey et al, 2005;Platt, Micciolo, & Tansella, 1992).…”
Section: Unemployment (N = 30)mentioning
confidence: 94%
See 2 more Smart Citations
“…While most studies have reported that higher unemployment is accompanied by an increase in suicide rates (Abe, 2004;Andres & Halicioglu, 2010;Berk et al, 2006;Blakely, Collings, & Atkinson, 2003;Chang, Sterne, Huang, Chuang, & Gunnell, 2010;Chen, Yip, Lee, Fan, & Fu, 2010;Chuang & Huang, 2007;Corcoran & Arensman, 2011;Fernquist, 2007;Kuroki, 2010;Lewis & Sloggett, 1998;Lin, 2006;Milner, McClure, et al, 2012;Preti & Miotto, 1999;Tsai & Cho, 2011;Yamasaki, Sakai, & Shirakawa, 2005;Ying & Chang, 2009), a smaller number of studies have found no or mixed evidence of this association Crawford & Prince, 1999;Lucey et al, 2005;Platt, Micciolo, & Tansella, 1992).…”
Section: Unemployment (N = 30)mentioning
confidence: 94%
“…For example, research using the indicator of non-marital births (a proxy used to represent the weakening of the family institution) has been associated with higher suicide rates in wealthy areas of the world (Messner et al, 2006;Stockard & O'Brien, 2002). However, research conducted in Ireland suggests that this association was also sensitive to changes in social norms over time (Lucey et al, 2005).…”
Section: Birth Rates (N = 11)mentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of Finland, which experienced an increase in suicide rate during an economic upswing between 1985 and 1990 and a decline during a subsequent period of recession,14 there were few empirical examples of suicide increasing during times of economic prosperity. Although research from Ireland showed no association between socioeconomic factors and suicide after accounting for time trends,15 most studies have suggested that suicide rates tend to decline during times of economic prosperity and increase during periods of recession 1618. In a recent review of the population-level mental health effects of economic downturns, Zivin et al19 inferred a positive association between economic crisis and the onset of psychopathology, including suicide.…”
Section: Introductionmentioning
confidence: 99%
“…A la inversa, otro estudio encontró que estar casado disminuyó el riesgo (Lorant et al, 2005). Un estudio encontró que la tasa de matrimonios se asocia de manera negativa al suicidio a nivel general y en hombres, y de manera positiva en mujeres (Lucey et al, 2005).…”
Section: Desigualdades En El Suicidiounclassified